2018
DOI: 10.1088/1361-6587/aaef53
|View full text |Cite
|
Sign up to set email alerts
|

Runaway electron beam control

Abstract: Plasma Physics and Controlled Fusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…This provides an approximate boundary between instabilities that act on REs in real space (< 30 MHz) and those that act on REs in phase space (> 30 MHz). Consequently both few MHz instabilities, 10-100s kHz MHD instabilities, and stationary applied 3-D fields can deconfine REs in effectively the same manner [42,8,82,70,43,16,41].…”
Section: General Prospects For Kinetic Instabilitiesmentioning
confidence: 98%
See 2 more Smart Citations
“…This provides an approximate boundary between instabilities that act on REs in real space (< 30 MHz) and those that act on REs in phase space (> 30 MHz). Consequently both few MHz instabilities, 10-100s kHz MHD instabilities, and stationary applied 3-D fields can deconfine REs in effectively the same manner [42,8,82,70,43,16,41].…”
Section: General Prospects For Kinetic Instabilitiesmentioning
confidence: 98%
“…In the time domain, increasing B T increases the decay rate at high E RE while increasing n e increases the RE decay rate at all E RE . Considering information in the spatial domain, energy-dependent radial gradients of the RE population are observed, enabling future model validation efforts to specifically target RE spatial transport effects due to either MHD instabilities [39,40,16,41], imposed 3-D fields [42,43], or inherent processes [44]. Furthermore, simultaneously viewing the same flux surface with different sight-line angles to the magnetic field enables deconvolution of pitch-angle information.…”
Section: Re Distribution Measurement Via Bremsstrahlungmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, much effort is directed towards the development of schemes to avoid, limit or mitigate the formation of such a beam. One proposed measure is using massive material injection (MMI) in the form of gas (massive gas injection – MGI) or frozen pellets (shattered pellet injection) to avoid or dissipate the runaway electrons (Hollmann et al 2015 a ; Lehnen et al 2015), and its efficiency has been demonstrated in medium-sized tokamaks (Hollmann et al 2015 b ; Reux et al 2015; Pautasso et al 2016; Esposito et al 2017; Paz-Soldan et al 2017; Carnevale et al 2018; Coda et al 2019; Mlynar et al 2019; Pautasso et al 2020). However, the plasma currents, temperatures and densities of future devices such as ITER will be significantly larger than what can be achieved in current experiments, and simulations are necessary to foresee the effectiveness of massive material injections for disruption mitigation under such conditions.…”
Section: Introductionmentioning
confidence: 99%
“…go has the ability to model elongated plasmas [39], however, this capacity was not used in the presented simulations. The modelled discharges featured slightly elongated plasmas, κ ≈ 1.16 in the JET discharges, according to pre-disruption equilibrium reconstructions 7 . Inclusion of the elongation in Toroidal magnetic field on axis B (T) 2.5 3 the simulations did not result in any qualitative changes in the simulation results, and thus it was decided to reduce the parameter space by omitting this parameter.…”
Section: Plasma Elongationmentioning
confidence: 71%